Overexpression of phosphomannomutase increases the production and bioactivities of Ganoderma exopolysaccharides. (15th October 2022) - Zhao, Li-Na; Cao, Yu-Biao; Luo, Qin; Xu, Yong-Liang; Li, Na; Wang, Cheng-Xiao; Xu, Jun-Wei
Abstract: In this study, we explored a novel approach to enhancing the production and bioactivities of Ganoderma exopolysaccharides. The homologous phosphomannomutase gene (PMM1) was cloned and overexpressed in Ganoderma for the first time. As a result, the maximum production of exopolysaccharides by the PMM1 transformant was 1.53 g/L, which was 1.41-fold higher than of a wild-type (WT) strain in a 5-L bioreactor. The transcription levels of PMM1 and PMM2 increased 40.5- and 2.4-fold, respectively, whereas the value of the GDP-D-mannose pyrophosphorylase gene did not change significantly in this transgenic strain. Furthermore, the major exopolysaccharide fractions from PMM1 transformants contained higher amounts of mannose (56.5 % and 21.1 %) than those from a WT strain (26.7 % and 9.3 %). Moreover, the major fractions from PMM1 transformants exhibited stronger regulation effects on macrophage. In conclusion, this study is helpful for the efficient production and application of Ganoderma exopolysaccharides and facilitates an understanding of polysaccharide biosynthesis regulation. Graphical abstract: Unlabelled Image